National Trends in the Surgical Management of Adult Lumbar Isthmic Spondylolisthesis: 1998 to 2011. Issue 6 (March 2016) - Thirukumaran, Caroline P.; Raudenbush, Brandon; Li, Yue; Molinari, Robert; Rubery, Paul; Mesfin, Addisu
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: A retrospective review. Objective: Isthmic spondylolisthesis (ISY) is a common orthopedic condition. Our objective was to identify trends in the surgical management of adult ISY in the United States and to evaluate trends in the surgical techniques utilized. Summary of Background Data: Various surgical approaches have been described for ISY but preferred trends are not known. Methods: Using the Nationwide Inpatient Sample (NIS), 47, 132 adult patients (≥18 years) with ISY undergoing lumbar spine fusion from 1998 to 2011 were identified. Our primary outcome of interest was the national trend in use of anterior (ASF), posterior (PSF), posterior with interbody (P/TLIF), and combined anterior-posterior fusion (A/PSF) surgeries for ISY patients. Poisson regression, modified Wald's test, and linear and logistic regression analysis with P < 0.05 were used for statistical analysis. Results: The annual rate of fusion surgeries for ISY increased 4.33 times—from 28.31 surgeries in 1998 to 122.69 surgeries per million US adults per year in 2011. Over the study period, annual rates of ASFs increased 2.65 times ( P < 0.001), PSFs increased 1.03 times ( P = 0.24), P/TLIFs increased 4.33 times ( P < 0.001), and A/PSF increased 2.93 times ( P < 0.001). In 2010 to 2011, the complication rate was significantly higher for A/PSF (18.86%, P < 0.001). PSFs had a higher complication rate of 3.61% and P/TLIFs (2.58%). The risk of complications was lower for females, elective admissions, and in hospitals in the South. Mean hospitalization charges adjusted to 2011 dollars were significantly higher for A/PSF (157, 560; 95% CI [95% confidence interval]: 14, 480–170, 360; P < 0.001), followed by P/TLIFs (103, 700; 95% CI: 9840–109, 030) and PSFs had lower mean hospitalization charges (87, 420; 95% CI: 8210–92, 770). Conclusion: Use of fusion for ISY has significantly increased and interbody fusion has become the most preferred approach over the study period. Hospital charges and complications were highest for combined anterior-posterior fusions. Level of Evidence : 3